2016
DOI: 10.1111/acer.13135
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Fetal Alcohol Syndrome—Pathogenesis, Risks, and Treatment

Abstract: Alcohol is a well-established teratogen that can cause variable physical and behavioral effects on the fetus. The most severe condition in this spectrum of diseases is known as fetal alcohol syndrome (FAS). The differences in maternal and fetal enzymes, in terms of abundance and efficiency, in addition to reduced elimination, allow for alcohol to have a prolonged effect on the fetus. This can act as a teratogen through numerous methods including reactive oxygen species (generated as by products of CYP2E1), dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 116 publications
(112 reference statements)
0
102
0
7
Order By: Relevance
“…Ethanol may also inhibit the transport of cofactors critical for fetal growth and development, such as biotin and vitamin B6. 2 The risk of infant births with low birth weight (<2500g for the term newborn) or small for gestational age increases linearly in mothers who consume a daily dose of alcohol (about 10g absolute alcohol) or more. 24 A survey of 1,964 pregnant women in a public maternity hospital in the city of São Paulo found that the higher the alcohol consumption, the lower the weight, the head circumference and the length of newborns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethanol may also inhibit the transport of cofactors critical for fetal growth and development, such as biotin and vitamin B6. 2 The risk of infant births with low birth weight (<2500g for the term newborn) or small for gestational age increases linearly in mothers who consume a daily dose of alcohol (about 10g absolute alcohol) or more. 24 A survey of 1,964 pregnant women in a public maternity hospital in the city of São Paulo found that the higher the alcohol consumption, the lower the weight, the head circumference and the length of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Other supplements, such as folic acid, Lglutamine, boric acid and choline also appear to minimize the harmful effects of alcohol on embryofetal development and may play a therapeutic role in the future. 2 Since there is no safe amount of alcohol intake during pregnancy and any amount can affect embryofetal development, 2,11 we recommend that the material published by the Ministry of Health to inform both health professionals and the general public points out the importance of abstaining from alcohol consumption throughout pregnancy explicitly, not only in the first trimester. Promoting advertising campaigns on the subject can also be an additional measure of health education.…”
Section: Variables Negative T-ace Positive T-ace P (N=758) (N=60)mentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge there is no published literature linking folic acid deficiency and formic acid to FASD, although numerous studies suggest alcohol-mediated oxidative stress as the possible mechanism (Dreosti 1993;Brocardo et al 2011;Muralidharan et al 2015;Gupta et al 2016;Sarmah et al 2016;Sogut et al 2017). Thus, treatment using nutrients that have antioxidant properties, such as folic acid, appear promising.…”
Section: Resultsmentioning
confidence: 99%